Alpha-Particle Therapy for Multifocal Osteosarcoma: A Hypothesis - Baranowska-Kortylewicz, Janina; Sharp, John G; McGuire, Timothy R; Joshi, Shantharam; Coulter, Don W (Cancer biotherapy & radiopharmaceuticals, 2020)
Osteosarcoma (OST) is the most common bone tumor in children and adolescents with a second peak of incidence in elderly adults usually diagnosed as secondary tumors in Paget's disease or irradiated bone. Subjects with metastatic disease or whose disease relapses after the initial therapy have a poor prognosis. Moreover, multifocal OST contains tumor-initiating cells that are resistant to chemotherapy. The use of aggressive therapies in an attempt to eradicate these cells can have long-term negative consequences in these vulnerable patient populations. Th-labeled molecular probes based on ligands to OST-associated receptors such as IGF-1R (insulin-like growth factor receptor 1), HER2 (human epidermal growth factor receptor 2), and PSMA (prostate-specific membrane antigen) are expected to detect and treat osseous and nonosseous sites of multifocal OST. Published reports indicate that Th has limited myelotoxicity, can be stably chelated to its carriers and, as it decays at targeted sites, Th produces Ra that is subsequently incorporated into the areas of increased osteoblastic activity, that is, osseous metastatic lesions. Linear energy transfer of α particles emitted by Th and its daughter Ra is within the range of the optimum relative biological effectiveness. The radiotoxicity of α particles is virtually independent of the phase in the cell cycle, oxygenation, and the dose rate. For these reasons, even resistant OST cells remain susceptible to killing by high-energy α particles, which can also kill adjacent quiescent OST cells or cells with low expression of targeted receptors. Systemic side effects are minimized by the limited range of these intense radiations. Quantitative single-photon emission computed tomography of Th and Ra is feasible. Additionally, the availability of radionuclide pairs, for example, Zr for positron emission tomography and Th for therapy, establish a strong basis for the theranostic use of Th in the individualized treatment of multifocal OST.